STUDENTS’ STRATEGIES IN LEARNING SPEAKING - Utama, Fajar Zikri; Shabir, M. (ENGLISH JOURNAL, 2017)
The study seeks to investigate the strategies used by university students in learning speaking. Questioner and interview were used to collect the data needed from nine students of eighth semester of an English Department at a university in West Java. The data interpreted qualitatively shows that high achiever students dominantly used compensation and social strategies. In the meantime, middle achiever students mostly used compensation and affective strategies and those lower achievers mostly used memory strategy. Their reasons for choosing such strategies vary but depend on their learning styles. Possible problem in students? use of certain strategies might be another interesting topic to be investigated in the future